A estratégia competitiva de uma empresa do sul do país no setor de medição de energia do mercado brasileiro - Silva, Hélio Lippert da (Universidade do Vale do Rio do Sinos, 2007)
Competitive positioning is the core theme of this dissertation, which seeks to analyse the strategy employed by Elster, a business unit of the CVC Partner international corporation that is located in southern Brazil and operates in the Brazilian electricity metering industry. Concepts by Porter (1986) were adopted as theoretical framework, according to three dimensions: the industry’s structure, generic strategies and the corporate strategy. The case study approach was used to address questions raised in the research. It is evident that the industry has been undergoing changes; the mechanical electricity meter, with its consolidated technology and prevailing position in sales, is being replaced at large by the electronic meter. It is anticipated that protective barriers once existing in the industry are bound to collapse, paving the way for newcomers and for a better positioning of some companies that already have a standing in the segment. Until now the benefits Elster enjoyed in being part of an internation
Keywords: estratégia competitiva; medidores de energia; mercado brasileiro; competitividade empresarial; Ciências Sociais Aplicadas